2006
DOI: 10.1139/o06-053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lactoferrin on EnteroaggregativeE. coli(EAEC)This paper is one of a selection of papers published in this Special Issue, entitled 7th International Conference on Lactoferrin: Structure, Function, and Applications, and has undergone the Journal’s usual peer review process.

Abstract: We previously demonstrated that lactoferrin inhibits adherence of enteropathogenic Escherichia coli to HEp-2 cells and decreases invasiveness of Shigella flexneri in HeLa cells by disruption of the type III secretory system (TTSS) of both enteropathogens. To determine whether these effects were specific to the TTSS, we assessed the activity of bovine lactoferrin on enteroaggregative E. coli (EAEC), enteropathogens whose virulence is not TTSS dependent. Bovine lactoferrin at a concentration of 1.0 and 0.1 mg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…We have histidine tagged dispersin, a virulence protein involved in the aggregative adherence phenotype, and the surface fimbria (AAF-II). We found that lactoferrin-induced loss and degradation of AAF-II but not of dispersin [46].…”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 65%
See 1 more Smart Citation
“…We have histidine tagged dispersin, a virulence protein involved in the aggregative adherence phenotype, and the surface fimbria (AAF-II). We found that lactoferrin-induced loss and degradation of AAF-II but not of dispersin [46].…”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 65%
“…Lactoferrin purified from human milk (Sigma-Aldrich Co. St. Louis, MO), recombinant human lactoferrin (Agennix, Houston, TX) and bovine lactoferrin (Tatua Cooperative Dairy Co, Morrinsville, New Zealand), inhibit the aggregative adherence "stacked-brick pattern" of EAEC in tissue cultured cells [45,46]. Bovine lactoferrin also inhibited EAEC biofilm formation and increased autoagglutination, further suggesting that surface adhesins were affected.…”
Section: Enteroaggregative E Coli (Eaec)mentioning
confidence: 99%
“…In contrast, apo-bLF increased the biofilm formation of S. mutans, while holo-bLF decreased the biofilm formation of S. mutans (18). bLF both with and without iron inhibited the biofilm formation of enteroaggregative E. coli (30). The inhibition of P. gingivalis and P. intermedia biofilm formation by LF was independent of the iron status of the protein, and the mechanism of action of LF against P. aeruginosa and S. mutans biofilm formation seems to be different from that against P. gingivalis and P. intermedia biofilm formation but similar to that against enteroaggregative E. coli biofilm formation.…”
Section: Vol 53 2009mentioning
confidence: 84%
“…Likewise, hLF at 0.13 mg/ml and apo-bLF, native bLF, and holo-bLF at 0.031 mg/ml inhibited P. intermedia biofilm formation. There are reports indicating that LF prevents the biofilm formation of Pseudomonas aeruginosa, Burkholderia cepacia, enteroaggregative Escherichia coli, and an oral pathogen, S. mutans (12,18,30,33,36). It has been documented that hLF inhibited the biofilm formation of P. aeruginosa by an iron-chelating mechanism (36).…”
Section: Vol 53 2009mentioning
confidence: 99%
“…12) Moreover, lactoferrin has been shown to decrease the virulence of some enteric pathogens by decreasing their ability to adhere to mammalian cells or to invade them. 17) Antimicrobial activity has also been demonstrated for the peptides formed by the hydrolysis of lactoferrin with pepsin. These peptides have a wide spectrum of activity, this activity being stronger than that of native lactoferrin and being effective even in the presence of iron.…”
mentioning
confidence: 99%